New Coincident and Leading Indicators for the Lebanese Economy - Matta, Samer (World Bank, Washington, DC, 2014)
Weak economic statistics in Lebanon impede economic analysis and decision making. This paper presents a new coincident indicator and a leading indicator for the Lebanese economy. A new methodology, based on the National Bureau of Economic Research-Conference Board approach, was used to construct these indicators. The indicators can be used as monthly proxies for the evolution of real gross domestic product with a relatively small time lag (four to five months). Notwithstanding the relatively small sample period, the results reveal promising statistical properties that should make these new indications valuable coincident and leading (one-year ahead) indicators for analyzing the dynamics of the Lebanese economy. However, given limitations on the length of the gross domestic product time series in Lebanon, the accuracy of these indicators in tracking the business cycle of the Lebanese economy is expected to improve over time as more data points become available.